Foot orthoses use for pediatric flexible flatfoot: comparative evaluation of quality of life for children and parents. Issue 3 (21st May 2020) - Camurcu, Yalkin; Ucpunar, Hanifi; Karakose, Resit; Ozcan, Seckin; Sahin, Vedat
Abstract : Supplemental Digital Content is available in the text. Abstract : This study aimed to comparatively evaluate the quality of life scores of patients with pediatric flexible flatfoot (PFF) according to the use of foot orthoses. We also aimed to compare quality of life scores of children and their parents. Nonobese children aged between 5 and 10 years old who were diagnosed as PFF according to physical and radiological examinations were included in this cross-sectional comparative study. All children and their parents completed the Turkish translation of Oxford ankle foot questionnaire (OxAFQ) which contains four domains (physical, school and play, emotional, and footwear). Patients were grouped according to the use of foot orthoses (group I: no foot orthoses group and group II: foot orthoses group). Comparison of OxAFQ scores demonstrated no significant differences between the two groups. However, the mean emotional scores of parents were significantly lower in group II ( P  = 0.007). In group I, the mean emotional score of children was significantly lower compared to their parents' scores ( P  = 0.001). In group II, the mean physical score of children was significantly lower compared to their parents' scores ( P  = 0.003). According to our results, we observed no significant difference in terms of quality of life scores between children using foot orthoses and not using foot orthoses. However, we observed significantly lower emotional scores in parents whose children were using foot orthoses. We recommend that physicians should be aware of low physical scores in children with PFF and should inform parents about this situation rather than considering foot orthoses to relieve parents' concern about foot deformity.